Morphological study of some Euphorbia taxa in Iran - SEYED MEHDI TALEBI; MITRA NOORI; SOMAYEH SHOJAEI DAVIJANI (Smujo International, 2016)
Abstract. Talebi SM, Noori M, Davijani SS. 2016. Morphological study of some Euphorbia taxa in Iran. Nusantara Bioscience 8: 103-110. Euphorbia (Euphorbiaceae) has nearly 2000 species and great morphological diversity present between its members. For this reason, species of this genus are classified into different infrageneric ranks. In the present study, morphological characteristics of fifteen taxa of this genus were examined in Iran. Thirty one qualitative and quantitative morphological characteristics from the vegetative and reproductive organs of the studied taxa were examined. ANOVA test showed significant variations for all of studied quantitative features. PCA-biplot of the studied traits confirmed that some of them were very useful for identification of the treated taxa. In addition, the obtained results did not confirm species classifications in sections/subsections according to Flora Iranica as well as Flora of Turkey and proved high morphological variations between these species; therefore traditional classification of species in subsection must be changed and our results confirmed previous molecular studies.